Italian Budgeting Policy Between Punctuations and Incrementalism - Cavalieri, Alice (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Alice Cavalieri has produced a careful and comprehensive analysis of public budgeting during the turbulent course of modern Italian history... It is bound to become a standard go-to resource for future studies of budgeting and policy processes more generally." -Bryan D. Jones, JJ "Jake" Pickle Regents Chair in Congressional Studies, University of Texas at Austin, USA "Alice Cavalieri's volume is an original piece of empirical research and a great contribution to the understanding of recent political changes in Italy." -Luca Verzichelli, Professor of Political Science, University of Siena, Italy This book assesses Italian budgetary policy over the last thirty years. Covering more than three decades of political change and national transformation, it considers the institutional and external factors that have shaped long-term budgetary changes. The book analyses the levels of expenditure allocation across varying budget categories, and compares the budget bill and budget law in order to shed new light on the specific dynamics that have influenced budgetary decision-making processes. Overall, the book provides important conclusions on the role of the budget as a governmental policy instrument, the consequences of multilevel governance over national budgetary policy, and the impact of national and international crises on budgetary changes. With Italy being one of the most important parliamentary democracies in Europe and a key actor within the European Union, these conclusions have important repercussions for other European parliamentary democracies. The book will appeal to scholars and students of European public policy, public administration and economic governance. Alice Cavalieri is a Researcher at the University of Trieste, Italy. She is the Italian country lead for the Oxford Covid-19 Government Response Tracker (OxCGRT), and a member of the Comparative Agendas Project. Her research interests include budget politics and policy change in Italy and Europe.
Chapter 1: Introduction -- Chapter 2: Policy-Making and Budget Changes -- Chapter 3: Budgeting Policy Within the Union: Italy in the European Context -- Chapter 4: Approaching an Explanation of Longitudinal Change in the Italian Budget -- Chapter 5: Incremental Changes or Punctuations? -- Chapter 6: To Change or Not to Change: Governments' Spending Intentions -- Chapter 7: The Impact of the Decision-Making Process -- Chapter 8: Conclusion.
Keywords: Political science; Political Science